GOVERNANÇA EM TECNOLOGIA DA INFORMAÇÃO: UM ESTUDO DE CASO DE UMA EMPRESA DE TRANSPORTE FERROVIÁRIO - Moraes, Emerson Augusto Priamo (2009)
This study presents and analyses a set of methodologies of information technology governance: BSC (Balanced Scorecard), COBIT (Control Objectives will be Information and Related Technology), ITIL (Information Technology Infrastructure Library), PMBOK (Project Management Body Of Knowledge), CMMI (Capability Maturity Model Integration) and ISO/IEC 20000. From this theoretical referential it is looked to identify the model of governance most adapted in order that been adopted by the MRS Logistica, which is characterized because of establishing daring marks of growth and expansion and which uses intensely IT in the activities of support to the business processes. Data were collected through a survey carried out among IT employees in several sectors and hierarchical levels and also a documentary inquiry, when are considering the internal elements that support IT Management, like strategic plan of business, internal processes and main projects, among others. It is ended that IT model of governance more adapted for the MRS Logistica is the COBIT, showed the most complete thing and obtained bigger degree of adherence in the analyzed dimensions. Meantime, it is important the possibility of use of more than a model together.